Dampak Keberadaan PT Eisindo terhadap Perekonomian Masyarakat Pesisir Di Desa Waijarang, Kecamatan Nubatukan, Kabupaten Lembata - Antonia, Yuliana Nensi; Sagajoka, Estherlina; Luciany, Yohanes Paulus (Program Studi Ekonomi Pembangunan Universitas Flores, 2022)
The study aims to determine the impact of the existence of PT Eisindo on the economy of coastel communities in Waijarang Village, Nubatukan District, Lembata Regency. Data collection methods used are interview, questionnaires, observation, and documentation. The analytical tool used a qualitative descriptive analysisto determine the impact of the existence of PT Eisindo on the economy of coastal communities in Waijarang Village, Nubatukan District, Lembata Regency. Theresults indicate that PT Eisindo is a fish processing factory built by the local government and village government whose management is carried out by the village community. PT. Eisindo has contributed greatly to the economy of the Waijarang Village community through three indicators, namely, income, employment and business opportunities. This can be seen from the positive impact felt by the people of Waijarang Village with the existence of PT. Eisindo, such as the provision of job vacancies, increasing income, and the community being able to open businesses that can increase the income of the people in Waijarang Village.